Cat Contact as A Risk Factor for Tinea Capitis Infection - Evy Ervianti; Addia Salsabila; Yuri Widia; Arthur Pohan Kawilarang (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Tinea capitis (TC) is common infection caused by dermatophytes on the scalp. Cat contact is one of the TC risk factors. Microsporum canis is the most abundant fungi in cats and humans as a zoophilic infection. Cats and carrier cats can infect humans, mostly children. Purpose: To evaluate cat contact as a risk factor for TC patients at the Dermatology and Venereology Outpatients Unit of Dr. Soetomo General Academic Hospital Surabaya in January 2017 - December 2018. Methods: A retrospective study by observation and recording data. The results obtained as a result of the data recap were then processed using tabulation to obtain conclusions. Result: The results obtained from TC cases in 2017 and 2018 are 20 patients. The results were cat contact in 9 patients (45%), aged > 5 years (55,6%), male (55,6%), and lived in Surabaya (88,9%), hair loss (88,9%), crust (100%), M. canis in culture (55,6%), Grey patch type (55,6%), combination of oral Griseofulvin and Ketoconazole 2% scalp solution (88,9%), and patients’ follow up (44,4%). Discussion: More people keeping cats will increase the risk of being infected with feline dermatophytosis. Combination therapy is the best treatment for M. canis. It is important to educate parents to be careful with pet cats that can become carriers. Conclusion: Cat contact was positive in almost half patients, mostly in a male and > 5 years old. The most common signs and symptoms were crust and hair loss, and grey patch.